The Evaluation Program of Coaching Football Achievement of East Nusa Tenggara Province Training Centre at the XX PON - Kadju, Eusabius Agusto Molo; Hartono, Mugiyo; Irawan, Fajar Awang (Journal of Physical Education and Sports, 2021)
East Nusa Tenggara Province's football has not fared well at the national level, especially the PON. The purpose of this study is several indicators, including coaches and athletes, training programs, infrastructure, organizational management, and funding. Method used research qualitative evaluation with countenance stage model, that consists of antecedent, transaction, and outcome. Data source: Coaches, athletes, and administrators from Asprov PSSI NTT. Data collected with observation, interviews and documentation. Data analysis process was data collecting, reduction, presentation, verification and conclusion. Result the study's findings include the following: adequate input from antecedents, coaches, and athletes; defined training program planning; availability of suitable but non-standardized infrastructural facilities; inadequate availability of organizational management; and insufficient funding. Transactions, recruitment of coaches and athletes based on agreed-upon terms and criteria, implementation of training programs guided by the program, using infrastructure, management coordinating with coaches and athletes, adhering to the budget plan, transparent and accountable. Outcomes, professional coaches' and athletes' performance, training regimens are out of expectations, coaches' and athletes' use of infrastructure, administrators' professional and responsible behavior, effective use of finances, and appropriate use of funds. Conclusion of the antecedents, coaches, and athletes were excellent, the training programs were adequate, the infrastructure sufficient, organizational management was inadequate, and funding was insufficient. Transactions, coaches, and athletes were excellent; training programs were excellent; infrastructure was excellent; organizational management was excellent, and funding was good. The outcomes, coaches, and athletes, training programs, infrastructure, organizational management, and funding are all excellent.